Pathogenesis of Acute Kidney Injury in Coronavirus Disease 2019 - Qian, Jing-Yi; Wang, Bin; Lv, Lin-Li; Liu, Bi-Cheng (Frontiers in Physiology, 2021)
Since the outbreak of Coronavirus Disease 2019 (COVID-19) in Wuhan, China, in December of 2019, it has rapidly become a global pandemic. Although acute respiratory disorder is the main manifestation of COVID-19, acute kidney injury (AKI) is another important extrapulmonary complication, which has a critical impact on the prognosis and mortality of patients. Current understanding about the exact pathogenesis of AKI in COVID-19 is unclear. Several studies have suggested that intrarenal, pre-renal and post-renal factors mediated collaboratively by direct virus attack, overloaded immune responses, drugs, sepsis, coagulation dysfunction, and underlying diseases may all be involved in the pathogenesis of AKI. This article reviews the current understanding of the pathogenesis of AKI in COVID-19.